Answer:
Vertex: (6, 18)
Step-by-step explanation:
Given the quadratic function, m(x) = -2(x - 3)(x - 9):
Perform the FOIL method on the two binomials, (x - 3)(x - 9) without distributing -2:
m(x) = -2[(x - 3)(x - 9)]
Combine like terms:
m(x) = -2(x² - 9x - 3x + 27)
m(x) = -2(x² - 12x + 27)
where: a = 1, b = -12, and c = 27
Since the <u>axis of symmetry</u> occurs at <em>x</em> = <em>h</em>, then we can use the following formula to solve for the x-coordinate (<em>h </em>) of the vertex, (h, k):
![x = \frac{-b}{2a}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b%7D%7B2a%7D)
Substitute a = 1 and b = -12 into the formula:
![x = \frac{-b}{2a}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b%7D%7B2a%7D)
![x = \frac{-(-12)}{2(1)} = \frac{12}{2} = 6](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-%28-12%29%7D%7B2%281%29%7D%20%3D%20%5Cfrac%7B12%7D%7B2%7D%20%3D%206)
Therefore, the x-coordinate (h) of the vertex is 6.
Next, substitute the value of <em>h</em> into x² - 12x + 27 to find the y-coordinate (<em>k </em>) of the vertex:
<em>k </em> = x² - 12x + 27
<em>k </em> = (6)² - 12(6) + 27
<em>k </em>= 36 - 72 + 27
<em>k</em> = 18
Therefore, the <u>vertex</u> of the quadratic function occurs at point (6, 18), in which it is the maximum point on the graph.